On the Asymptotic Behavior and Parameter Estimation of a Double-Sided LCC-Compensated Wireless Power Transfer System - Feng-Rung Hu (MDPI AG, 2021)
This study investigates the statistic behavior and parameter estimation problems of a double-sided, LCC-compensated, wireless power transfer system. Based on the commonly used wireless charging circuit model, this study proposes a five-step parameter estimation method, which is applicable to automotive static wireless charging systems. The eight parameters in the circuit model of this study are the most important key components of the wireless charging system. The study also found that, under certain conditions, the statistic mode of wireless charging systems has a specific distribution. However, the current status of these eight components for wireless charging of electric vehicles will have complex parameter drift problems. These drift problems will deteriorate the performance of the vehicle power systems. This study probes these factors and proposes some related mathematical theories. The noted factors can be applied to the analysis of the wireless charging system and provide alternative solutions to explain the deteriorations from coil misalignments. Both simulations and experiments are given to show the evaluated issues of the proposed study.